A decision-support framework for the restoration of Cystoseira sensu lato forests - Christopher J. Smith; Jana Verdura; Nadia Papadopoulou; Simonetta Fraschetti; Emma Cebrian; Erika Fabbrizzi; Margalida Monserrat; Matilde Drake; Silvia Bianchelli; Roberto Danovaro; Dania Abdul Malak; Enric Ballesteros; et al. (Frontiers in Marine Science, 2023)
Macroalgal forests characterised by species of the genus Cystoseira sensu lato form important shallow coastal rocky habitats in the Mediterranean Sea. These forests support a high biodiversity and provide important ecosystem services and societal benefits. Currently these habitats are often in a poor condition in many areas, due to loss and degradation from both anthropogenic and climate stressors. Restoration has recently moved to the forefront of the United Nations and European Union agendas to reverse this trend, particularly in the last decade with the implementation of various international policies. However, this has been in the form of generic targets (e.g., restoration of 30% of degraded habitats by 2030) and has not been linked to specifically what habitat or species to restore, where and how. Initial targets have been missed, new targets are expected through the proposed EU Nature Restoration Law, but overall guidance is still lacking. There are few specific guides to marine habitat restoration limited to mostly seagrass, corals and shellfish. As a priority action for the recovery of coastal marine ecosystems a decision-support framework has been developed for the restoration of Mediterranean macroalgal forests, comprising a stepwise decision tree with additional descriptions of key elements to be considered for a restoration action. The decision tree includes steps concerning current and historical forest presence, site local condition assessment and choice of actions. Key considerations include restoration implementation (competence, society and support, finance and governance), success evaluation (at the target species and the ecosystem level) and long-term management. The framework builds on existing work on Cystoseira s.l. restoration, the work carried out in the EU AFRIMED project, but also on principles and guidelines in place for both generic and specific marine habitats. The work reported here has involved the expertise of scientists and information from stakeholders. Gaps were identified and recommendations were made, dealing with stressors, coordinating and networking stakeholders, integrating top down policy and bottom up initiatives, funding of restoration actions, establishing synergies between restoration, conservation and marine spatial planning and finally communication and publicity.